(untitled) (Revista de Medicina Clinica, 2025)
Introduction: Cryptococcus is an encapsulated yeast with opportunistic capabilities, responsible for severe infections such as meningoencephalitis and disseminated cryptococcosis. The most relevant species are Cryptococcus neoformans and Cryptococcus gatti; the former mainly inmunosuppressed individuals, while the latter can infect immunocompetent individuals. The infection occurs through the respiratory route, usually asymptomatically or with mild symptoms; however, in individuals with a weakened immune system, the fungus can spread to the central nervous system. Case Report: This is the case of a male patient with a history of ischemic cerebrovascular event and type 2 diabetes mellitus who presented with headache, predominantly holocranial, nausea, vomiting, disorientation, and impaired consciousness. Brain MRI showed a lesion with increased intensity in the right lateral ventricle. A lumbar puncture was performed with results suggestive of fungal meningitis. Subsequently, the cerebrospinal fluid culture was positive for Cryptococcus neoformans using India ink and showed growth of this pathogen on Sabouraud dextrose agar. Treatment with amphotericin B and 5-flucytosine was initiated; however, the patient developed complications that ultimately led to his death Conclusions: Cryptococcal meningoencephalitis is a condition with high mortality. Therefore, finding suggestive signs in the central nervous system should be an indicator to initiate intensive treatment regimens that can impact the patient’s prognosis.